Nieważność i wygaśnięcie konkordatu polskiego z 1993 r. - Borecki, Paweł (Studia Prawa Publicznego, 2020)
From time to time, there is a proposal in the public debate in Poland to break the 1993 concordat, and this has also recently been the case. However, in the current systemic and political reality of contemporary Poland, the issue of the invalidity or expiry of the Polish concordat is one purely for theoretical (academic) discussion. It is worth analyzing this through the prism of the Vienna Convention on the Law of Treaties of 1969 and the Constitution of the Republic of Poland of 1997. The only hypothetical grounds for an annulment of the 1993 Concordat would be the allegation that it was concluded in violation of Art. 46 of the Vienna Convention, i.e. in breach of the rules of national law concerning the competence to conclude a treaty of fundamental importance. The Government of the Republic of Poland did not raise this objection within a reasonable time. There are also no circumstances that could constitute obvious reasons for considering the Polish concordat of 1993 as expired. One might try to defend the position that the concordat may be terminated unilaterally, despite the fact that it does not contain an appropriate clause in this regard. It can be compared to a friendship treaty. Such contracts are, by their very nature, subject to termination. It also seems that if need be, the Polish side might be able to terminate the concordat due to a fundamental change in circumstances, e.g. by referring to the rapidly progressing secularization process of Polish society. A very serious barrier to the termination of the concordat by the Polish side is the Constitution of the Republic of Poland of 1997. In Art. 25 sec. 4 it provides for the obligation to define the relations between the state and the Catholic Church, especially in the form of an international agreement with the Holy See. The hypothetical termination of the 1993 concordat would require prior appropriate amendment of Poland’s constitution and the consent of a number of state bodies. In the current legal situation in Poland, the termination of the treaty with the Vatican is very difficult in procedural terms, and is politically unrealistic.